Development of YouTube Learning Media Based on Practicum of Electrolyte and Non-Electrolyte Materials - Alfina Ayu Dewanti; Setia Rahmawan (IKIP Mataram, 2024)
Education in Indonesia is currently ranked among the lowest in terms of quality, as evidenced by PISA 2018. Therefore, it is crucial to introduce technological innovations, such as instructional videos, to improve the state of education in the country. This project aims to create animated films that can serve as instructional resources for electrolyte and non-electrolyte solution materials, specifically designed for classroom use. The research method employed is Research and Development (R&D), utilizing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results of this study demonstrate the high validity of the learning videos developed, as indicated by the validation tests carried out by media experts (81.4%) and material experts (96.9%). These results are further supported by a questionnaire-based assessment of student responses, with an overall satisfaction rate of 98.67%. Therefore, it can be concluded that the development of practicum-based YouTube animation videos on electrolyte and non-electrolyte materials, using the ADDIE model, is highly suitable for educational purposes.